2018
DOI: 10.3329/ptcb.v28i1.37196
|View full text |Cite
|
Sign up to set email alerts
|

Over Expression of p5cs Gene to Increase Cold Stress Tolerance in Iranian Species of Petunia

Abstract: In order to examine the relationship between proline and cold stress in Iranian (local) genotype of petunia, p5cs gene was transferred to petunia through Agrobacterium-mediated transformation. The leaf discs from four weeks and shoot apices from 7-day-old petunia in vitro plants were co-cultivated with Agrobacterium strain LBA4404 harboring a plasmid pBI121 as the vector system for transformation of petunia. pBI121 plasmid containing β-glucuronidase (gus) gene as a reporter gene and Δ1-pyrroline-5-carboxylate … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(1 citation statement)
references
References 7 publications
0
1
0
Order By: Relevance
“…It has been previously proven that P5CS was a gene encoding the key enzyme involved in proline (Rai & Penna, 2013;Signorelli & Monza, 2017); however, the proline accumulation takes part in response to many abiotic stresses, thus the P5CS gene plays a key role in stress tolerance for growth and development of plants. It has been reported that overexpression of P5CS enhances the abiotic stress resistance of plant, such as LT (Jamshidnia et al, 2018), salt (Guan et al, 2018), drought stress (Wei at al. et al, 2016), and so on.…”
Section: Discussionmentioning
confidence: 99%
“…It has been previously proven that P5CS was a gene encoding the key enzyme involved in proline (Rai & Penna, 2013;Signorelli & Monza, 2017); however, the proline accumulation takes part in response to many abiotic stresses, thus the P5CS gene plays a key role in stress tolerance for growth and development of plants. It has been reported that overexpression of P5CS enhances the abiotic stress resistance of plant, such as LT (Jamshidnia et al, 2018), salt (Guan et al, 2018), drought stress (Wei at al. et al, 2016), and so on.…”
Section: Discussionmentioning
confidence: 99%